Emotional Self-Care: Exploring the Influencing Factors Among Individuals With Cancer - Sebastian, Ann Tresa; Rajkumar, Eslavath; John, Romate; Daniel, Monica; George, Allen Joshua; Greeshma, Rajgopal; James, Treasa (Frontiers in Psychology, 2022)
Cancer is a non-communicable disease that is a top cause of distress and mortality across the globe. The abnormal cell growth associated with cancer causes immense pain and disability. There are pharmacological as well as non-pharmacological methods to deal with pain and manage the symptoms and conditions. Among the prevailing non-pharmacological techniques, self-care behaviors are viewed as a key source in symptom management and enhancing quality adherence to treatment. Among the intervention strategies formulated to enhance self-care, very less impact was shown because of the limited focus confined only to physical self-care. Bringing in the emotional self-care and addressing the emotional health of the individual can improve the effectiveness of interventions on a holistic level. Hence the current study tried to explore the factors that influence emotional self-care among individuals with cancer. Following an exploratory research design, the data was collected with the help of semi-structured interviews. Data was collected from 15 participants (Male=4 & Female= 11). Through thematic analysis, 8 major themes were identified: Physiological factors, Social factors, Family factors, Psychological factors, Individual factors, Socioeconomic factors, Cultural factors, and Spiritual factors. The findings explained about the emotional self-care among cancer patients and also how different factors which were identified influence their emotional self-care practices.